Editorial: Wheat biofortification to alleviate global malnutrition - Ibba, Maria Itria; Gupta, Om Prakash; Govindan, Velu; Johnson, Alexander A.T.; Brinch-Pedersen, Henrik; Nikolic, Miroslav; Taleon, Victor (Frontiers Media, 2022)
According to the latest FAO report on the state of food security and nutrition in the world (1), more than 720 million people faced hunger, and around 3 billion people did not have access to a healthy diet. All these problematics, exacerbated by the current COVID-19 crisis, led to an increase in the number of people affected by the so-called hidden hunger, caused by an inadequate intake of essential micronutrients (MNs) such as iron (Fe), zinc (Zn), selenium (Se) and provitamin A. Biofortification, intended as the improvement of the nutritional quality of food crops through either conventional breeding, agronomic practices or modern biotechnologies, represents a sustainable, cost-effective and long-term approach to alleviate micronutrient-deficiency. Staple crops are typically the major target of most biofortification studies, given their central role in human diet. Wheat, specifically, contributes to around 20% of the total energy and protein intake and to around 30% of the Fe and Zn intake worldwide. However, the current level of MNs present in most wheat-derived food products is not enough to meet the minimum daily intake, especially in the poorest regions of the world. For these reasons, continuing to work on wheat biofortification is fundamental to ensure the production of nutritious and sustainable food and to contribute to the reduction of MNs deficiency.